Ionic Nature of a Gemini Surfactant at the Air/Water Interface - Phan, Chi; Nguyen, C.; Nakahara, H.; Shibata, O.; Nguyen, T. (American Chemical Society, 2016)
© 2016 American Chemical Society.The ionic state of an adsorbed gemini surfactant at the air/water interface was investigated using a combination of surface potential and surface tension data. The combined model was developed and successfully described the experimental data. The results verified the existence of three ionic states of the gemini surfactant in the interfacial zone. Furthermore, the model can quantify the adsorbed concentrations of these species. At low concentrations, the fully dissociated state dominates the adsorption. At high concentrations, the fully associated state dominates, accounting for up to 80% of the total adsorption. In the middle range, the adsorption is dominated by the partially associated state, which has a maximum percentage of 80% at a critical micelle concentration of 0.5. The variation in the ionic state is a unique characteristic of gemini surfactants, which can be the underlying mechanism for their advantages over conventional surfactants.